Nox4 Promotes RANKL-Induced Autophagy and Osteoclastogenesis via Activating ROS/PERK/eIF-2α/ATF4 Pathway - Sun, Jing; Chen, Wugui; Li, Songtao; Yang, Sizhen; Zhang, Ying; Hu, Xu; Qiu, Hao; Wu, Jigong; Xu, Shangcheng; Chu, Tongwei (Frontiers in Pharmacology, 2021)
Receptor activator of nuclear factor-κB ligand (RANKL) has been found to induce osteoclastogenesis and bone resorption. However, the underlying molecular mechanisms remain unclear. Via conducting a series of biochemical experiments with in vitro cell lines, this study investigated the role and mechanism of NADPH oxidase 4 (Nox4) in RANKL-induced autophagy and osteoclastogenesis. In the current study, we found that RANKL dramatically induced autophagy and osteoclastogenesis, inhibition of autophagy with chloroquine (CQ) markedly attenuates RANKL-induced osteoclastogenesis. Interestingly, we found that the protein level of Nox4 was remarkably upregulated by RANKL treatment. Inhibition of Nox4 by 5-O-methyl quercetin or knockdown of Nox4 with specific shRNA markedly attenuated RANKL-induced autophagy and osteoclastogenesis. Furthermore, we found that Nox4 stimulated the production of nonmitochondrial reactive oxygen species (ROS), activating the critical unfolded protein response (UPR)-related signaling pathway PERK/eIF-2α/ATF4, leading to RANKL-induced autophagy and osteoclastogenesis. Blocking the activation of PERK/eIF-2α/ATF4 signaling pathway either by Nox4 shRNA, ROS scavenger (NAC) or PERK inhibitor (GSK2606414) significantly inhibited autophagy during RANKL-induced osteoclastogenesis. Collectively, this study reveals that Nox4 promotes RANKL-induced autophagy and osteoclastogenesis via activating ROS/PERK/eIF-2α/ATF4 pathway, suggesting that the pathway may be a novel potential therapeutic target for osteoclastogenesis-related disease.